2019
DOI: 10.1002/ece3.5817
|View full text |Cite
|
Sign up to set email alerts
|

Responses of four dominant dryland plant species to climate change in the Junggar Basin, northwest China

Abstract: AimDryland ecosystems are exceedingly sensitive to climate change. Desertification induced by both climate changes and human activities seriously threatens dryland vegetation. However, the impact of climate change on distribution of dryland plant species has not been well documented. Here, we studied the potential distribution of four representative dryland plant species (Haloxylon ammodendron, Anabasis aphylla, Calligonum mongolicum, and Populus euphratica) under current and future climate scenarios in a temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 56 publications
1
17
1
Order By: Relevance
“…Habitat formation for a particular species is often affected by bioclimate, altitude, topography, soil, etc., and human factors cannot be neglected because they are related to people with the greatest economic interest (Jeffrey et al, 2015;Liu et al, 1999). Our results show that precipitation was most important for the distribution of H. ammodendron and C. deserticola, which is different from the conclusion that temperature was a key variable (Xiao et al, 2019;Yang, 2017). Among the various variables adopted in the model, bioclimate factors were significant for the three groups.…”
Section: Key Environment Variables and Ecological Characteristicscontrasting
confidence: 67%
See 1 more Smart Citation
“…Habitat formation for a particular species is often affected by bioclimate, altitude, topography, soil, etc., and human factors cannot be neglected because they are related to people with the greatest economic interest (Jeffrey et al, 2015;Liu et al, 1999). Our results show that precipitation was most important for the distribution of H. ammodendron and C. deserticola, which is different from the conclusion that temperature was a key variable (Xiao et al, 2019;Yang, 2017). Among the various variables adopted in the model, bioclimate factors were significant for the three groups.…”
Section: Key Environment Variables and Ecological Characteristicscontrasting
confidence: 67%
“…ammodendron and C . deserticola , which is different from the conclusion that temperature was a key variable (Xiao et al, 2019 ; Yang, 2017 ). Among the various variables adopted in the model, bioclimate factors were significant for the three groups.…”
Section: Discussionmentioning
confidence: 58%
“…These climatic variables reflect the general harshness in dryland environments (PP), water availability during the driest period, a major bottleneck of seedling recruitment in drylands (PDQ), and temperature and other environmental oscillations that could cause additional physiological stress (MDR, MTCQ, TS, elevation and PS). Most of these climatic variables have been identified previously as major drivers of plant distributions and plant-plant interactions in drylands (e.g., Whitford, 2002;Xiao et al, 2019).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…mental conditions of the original place of Populus euphratica and the environmental conditions of Yulin, we found that the habitat conditions in Yulin were better [13]. Populus euphratica should have adapted to the habitat of Yulin and could be feasibly introduced in Yulin.…”
Section: Experimental Designmentioning
confidence: 85%
“…In China, natural Populus euphratica forests are mainly distributed in Xinjiang and northwest Inner Mongolia [11,12]. By comparing the climatic and environmental conditions of the original place of Populus euphratica and the environmental conditions of Yulin, we found that the habitat conditions in Yulin were better [13]. Populus euphratica should have adapted to the habitat of Yulin and could be feasibly introduced in Yulin.…”
Section: Introductionmentioning
confidence: 96%